Korea's jewel in the East Sea, Dokdo ([Seoul?] Forum for Maritime Boundary Delimitation Studies)
Presents a general survey and introduction to the natural environment of and Korea's claim to sovereignty over Dokdo Island, known internationally as Tok Island.
English, Spanish, French.
System requirements: IBM PC or compatible with 486DX or higher, 8MB of RAM, 256 color VGA (32,000 color recommended), CD-ROM drive 4x or higher, sound card, OS : MS Window95.
Keywords: Tok Island (Korea) -- Description and travel; Tok Island (Korea) -- International status